Concentrations and isotope ratios of mercury in sediments from shelf and continental slope at Campos Basin near Rio de Janeiro, Brazil. (July 2017) - Araujo, Beatriz Ferreira; Hintelmann, Holger; Dimock, Brian; Almeida, Marcelo Gomes; Rezende, Carlos Eduardo
Abstract: Mercury (Hg) may originate from both anthropogenic and natural sources. The measurement of spatial and temporal variations of Hg isotope ratios in sediments may enable source identification and tracking of environmental processes. In this study we establish the distribution of mercury concentrations and mercury isotope ratios in surface sediments of three transects along the continental shelf and slope in Campos Basin-RJ-Brazil. The shelf showed on average lower total Hg concentrations (9.2 ± 5.3 ng g −1 ) than the slope (24.6 ± 8.8 ng g −1 ). MMHg average concentrations of shelf 0.15 ± 0.12 ng g −1 and slope 0.13 ± 0.06 ng g −1 were not significantly different. Distinct differences in Hg isotope ratio signatures were observed, suggesting that the two regions were impacted by different sources of Hg. The shelf showed more negative δ 202 Hg and Δ 199 Hg values ranging from −0.59 to −2.19‰ and from −0.76 to 0.08‰, respectively. In contrast, the slope exhibited δ 202 Hg values from −0.29 to −1.82‰ and Δ 199 Hg values from −0.23 to 0.09‰. Mercury found on the shelf, especially along the "D" and "I" transects, is depleted in heavy isotopes resulting in more negative δ 202 Hg compared to the slope. Isotope ratios observed in the "D" and "I" shelf region are similar to Hg ratios commonly associated with plants and vegetation and very comparable to those detected in the estuary and adjoining mangrove forest, which suggests that Hg exported from rivers may be the dominating source of Hg in near coastal regions along the northern part of the shelf. Highlights: Riverine delivery of Hg could be an important source of Hg input to continental shelf. Hg and MMHg concentrations in CB sediments are comparable to background levels. Hg isotope ratios are an important tool to differentiate sources and processes of Hg.